Cascade Hydroamination/Redox Reaction for the Synthesis of Cyclic Aminals Catalyzed by a Combined Gold Complex and Brønsted Acid. Issue 17 (19th March 2013) - He, Yu‐Ping; Wu, Hua; Chen, Dian‐Feng; Yu, Jie; Gong, Liu‐Zhu
<x xml:space="preserve">Abstract</x> Relay catalysis: An unprecedented protocol for the synthesis of cyclic aminals has been realized under the relay catalysis of a gold(I)/Brønsted acid binary system to generate cyclic aminals in excellent yields of up to 99 % with moderate to high diastereoselectivity (see scheme; up to 95:5 d.r.).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>